Could leprosy reaction episodes be exacerbated by oral infections? - Ana Carolina Fragoso Motta; Renata Bazan Furini; João Carlos Lopes Simão; Mariana Bellini Vieira; Maria Aparecida Nunes Ferreira; Marilena Chinali Komesu; Norma Tiraboschi Foss (Revista da Sociedade Brasileira de Medicina Tropical, 2011)
INTRODUCTION: This study evaluated whether leprosy reactions could be associated with oral infection. METHODS: Leprosy patients (n = 38) with (Group I) and without (Group II) oral infections were selected. Reactions were identified from the clinical and histopathological features associated with serum C-reactive protein (CRP) and10kDa interferon-gamma-induced protein (IP-10) levels, determined before and after elimination of the foci of infection. RESULTS: Group I presented more reactions than group II did, and improvement of the reactions after dental treatment. Serum CRP and IP-10 did not differ before and after the dental treatment, but differed between the groups. CONCLUSIONS: Oral infection could be an exacerbating factor in leprosy reactions.